Symptoms of posttraumatic stress disorder among hospitalized patients with cancer. Issue 16 (15th June 2018) - Nipp, Ryan D.; El‐Jawahri, Areej; D'Arpino, Sara M.; Chan, Andy; Fuh, Charn‐Xin; Johnson, P. Connor; Lage, Daniel E.; Wong, Risa L.; Pirl, William F.; Traeger, Lara; Cashavelly, Barbara J.; Jackson, Vicki A.; et al.
Abstract : BACKGROUND: Patients with cancer experience many stressors placing them at risk for posttraumatic stress disorder (PTSD) symptoms, yet little is known about factors associated with PTSD symptoms in this population. This study explored relationships among patients' PTSD symptoms, physical and psychological symptom burden, and risk for hospital readmissions. METHODS: We prospectively enrolled patients with cancer admitted for an unplanned hospitalization from August 2015‐April 2017. Upon admission, we assessed patients' PTSD symptoms (Primary Care PTSD Screen), as well as physical (Edmonton Symptom Assessment System [ESAS]) and psychological (Patient Health Questionnaire 4 [PHQ‐4]) symptoms. We examined associations between PTSD symptoms and patients' physical and psychological symptom burden using linear regression. We evaluated relationships between PTSD symptoms and unplanned hospital readmissions within 90‐days using Cox regression. RESULTS: We enrolled 954 of 1, 087 (87.8%) patients approached, and 127 (13.3%) screened positive for PTSD symptoms. The 90‐day hospital readmission rate was 38.9%. Younger age, female sex, greater comorbidities, and genitourinary cancer type were associated with higher PTSD scores. Patients' PTSD symptoms were associated with physical symptoms (ESAS physical: B = 3.41; P < .001), the total symptom burden (ESAS total: B = 5.97; P < .001), depression (PHQ‐4 depression: B = 0.67; P < .001), and anxiety symptoms (PHQ‐4 anxiety: B = 0.71; P < .001). Patients' PTSD symptoms were associated with a lower risk of hospital readmissions (hazard ratio, 0.81; P = .001). CONCLUSIONS: A high proportion of hospitalized patients with cancer experience PTSD symptoms, which are associated with a greater physical and psychological symptom burden and a lower risk of hospital readmissions. Interventions to address patients' PTSD symptoms are needed and should account for their physical and psychological symptom burden. Cancer 2018. © 2018 American Cancer Society . Abstract : This study shows that a substantial proportion of hospitalized patients with cancer experience symptoms of posttraumatic stress disorder. Patients' posttraumatic stress disorder symptoms are associated with a greater physical and psychological symptom burden and a lower risk of unplanned hospital readmissions.